Idarat al-awqaf fi Nayjiriya wa-tatawwuratiha : mushkilat wa-hulul = Administration of awqaf in Nigeria and their development : problems and solutions / Ahmad Abubakar Umar - Umar, Ahmad Abubakar (2013)
This humble research discuss the Administration of Awqaf and their Development in Nigeria and their Problems and Solutions to those problems, all from the administrative, development and investment perspective, and legitimacy of awqaf existing in the country, the study began with the conditions of the Waqf in Nigeria before colonialism, and During its days in terms of the policy of the colonists toward endowments, and Stoic Managers of Endowments in those days, as well as after the country's independence, and the beginning of State governments intervention in the endowment activities, in regarding to the legal aspect the research provide a valuable information regarding the position of the Nigerian federal government constitution toward creating, managing and developing Awqaf asset in the country, and the courts that have jurisdiction in matters relate to endowments, and its position through some of the cases considered, and who are the sole trustees and commissioners of Awqaf in governmental ministries and non-governmental charity organization,(NGOs) locals and internationals, in terms of their managerial structure and hierarchy as well as their budget allocation and source of fund. Legal provisions that support awqaf activities also have been highlighted. In terms of development and investment the research had deal with the matters concining the concept and methods of development and investment in the endowment system. The research also addressed classical and contemporary application methods of developments and investments of Awqaf institutions which are carried out by both systems, (governmental bodies and non-governmental charity organization) nevertheless a certain attention had been paid in respect to the problems faced by the endowments directly and indirectly, presently or is afraid of them in the future, and then propose solutions to those problems. A special section has also been developed to propose Contemporary systems for administration, development and investment of awqaf institutions in Nigeria.